No Retreat, No Surrender: Concessions, Resistance, and the End of the Postwar Settlement - Draper, Alan (Labour / Le Travail, 2003)
The article reviews and comments on several books including "Betrayal of Local 14: Paperworkers, Politics, & Personal Replacements," by Julius Getman, "Copper Crucible: How the Arizona Miners' Strike of 1983 Recast Labor-Management Relations in America," by Timothy J. Minchin and "Forging a Common Bond: Labor & Environmental Activism During the BASF Lockout," by Jonathon D. Rosenblum.
Keywords: BETRAYAL of Local 14: Paperworkers; Politics & Personal Replacements (Book); BOOKS – Reviews; COPPER Crucible (Book); FORGING a Common Bond: Labor & Environmental Activism During the BASF Lockout (Book); GETMAN; Julius; MINCHIN; Timothy J.; Nonfiction; ROSENBLUM; Jonathon D.